PENGARUH PENERAPAN BAHAN AJAR BERBASIS PENDEKATAN SAINTIFIK MELALUI ICT DALAM MODEL PEMBELAJARAN INQUIRY TERHADAP KOMPETENSI FISIKA SISWA KELAS X SMA N 1 PADANG - Rozi Prima Yenni; Masril Masril; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2016)
The achievement of students’ physics competence in high school learning process is still relatively low. One contributing factor is the learning model used by teachers cannot invite students to be able to find and solve the problem of Physics and also the instructional materials used by teachers not yet fully using the scientific approach. Besides, the use of ICT in learning is not optimal. To overcome these problems, it is applied inquiry learning model using teaching materials of scientific approach that is integrated with ICT. Therefore, the purpose of this study is to determine the effect of applying a scientific approach based teaching materials through ICT in inquiry learning model of grade X SMAN 1 Padang. To achieve this goal, the Pre-experimental research design was conducted. In this study, the experiments were carried out with no exercise control over the influenced variables and the preferred was treatment without any control group. The population in this study was students of grade X SMAN MIA I Padang enrolled in the academic year 2015/2016. The sampling technique is by purposive sampling technique. The research instrument is a test that sheet write to the competence of knowledge, attitude observation sheet for competence, and performance pieces for competency skills. Data analysis techniques used in this study is the linear regression test for competency knowledge and skills and used the graph to the competence of attitude. Based on the study that has been done, the data obtained for the all three students’ physics competences. First, on the competence of the students’ attitude has increased in general to each meeting. Second, on the competence of students’ knowledge, there are affections of teaching materials of scientific approach based through ICT in inquiry learning model for the competence of knowledge with values rtest> rtable, the percentage of impact is> 15%. Third, on the competency skills with good criteria, but rtest >rtable, the percentage of impact is>13%, so that it shows the influence of teaching materials scientific approach -based through ICT to inquiry learning model to competence skills